4D cardiac magnetic resonance imaging, 4D and 2D transthoracic echocardiography: a comparison of in-vivo assessment of ventricular function in rats - Stegmann, Hedwig; Bäuerle, Tobias; Kienle, Katharina; Dittrich, Sven; Alkassar, Muhannad (Laboratory Animals, 2019)
Preclinical cardiovascular research is the foundation of our understanding and broad knowledge of heart function and cardiovascular disease. Reliable cardiac imaging modalities are the basis for applicable results. Four-dimensional cardiac magnetic resonance (4D CMR) has been set as the gold standard for in-vivo assessment of ventricular function in rodents. However, technical improvements in echocardiography now allow us to image the whole heart, which makes four-dimensional echocardiography (4DE) a possible alternative to 4D CMR. To date, no study has systematically assessed 4DE in comparison with 4D CMR in rats. In total we studied 26 juvenile Sprague-Dawley rats (Crl: CD (SD) IGS). Twenty rats underwent echocardiographic imaging (2D and 4D) and 4D CMR. Five of those rats underwent a ligation of the superior and inferior vena cava to reduce the cardiac inflow as a disease model. Six additional rats were used to assess reproducibility of echocardiography and underwent three echocardiographic examinations. 4D CMR was performed on a 7T scanner; 2D and 4D echocardiography was conducted using a 40 MHz transducer. Correlation between 4D CMR, 4DE and 2DE for left-ventricular ejection fraction (LVEF) was assessed. An excellent correlation was observed between 4DE and 4D CMR (r = 0.95, p < 0.001). Correlation of 2DE and 4D CMR was weak (r = 0.57, p < 0.01). 4DE provides results that are equally precise as 4D CMR and highly reproducible with less technical effort than 4D CMR.
CRIS-Team Scopus Importer:2019-05-09
Keywords: cardiac magnetic resonance; echocardiography; four-dimensional cardiac imaging; left ventricular function; rat